Integrasi Teori Konstruktivisme dalam Pendidikan Agama Kristen: Pendekatan Kontekstual dalam Pembentukan Iman (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This article examines the integration of constructivist theory in Christian Religious Education (PAK) by emphasizing the role of personal experience as the basis for faith formation. Through a reflective-theological qualitative approach, this research combines the constructivist thought of Piaget, Vygotsky, and Fosnot with a theological perspective on the incarnation of Christ and the work of the Holy Spirit. The analysis suggests that constructivism can be theologically reinterpreted into a new paradigm called the Theo-Constructive Epistemology of Incarnational Faith, in which faith is not simply taught cognitively, but is constructed through life experiences infused by the presence of God. This approach emphasizes that the learning of faith is relational, participatory, and contextual, in line with the nature of God who works in human history. The findings of this study offer a new direction for PAK praxis to be more relevant to digital contexts and cultural plurality, without losing its theocentric orientation. Thus, the integration of constructivism and incarnational theology opens up space for more dynamic, contextual, and transformative learning of faith, while strengthening the relevance of PAK in facing the challenges of modern times.